الالتزم الوظيفي وعلاقته بالرضا الوظيفي - مشتي, لروية; خطار, زهية (جامعة الوادي - University of Eloued, 2020)
ملخص الدراسة : هدفت الدراسة الى التعرف، مدى وجود علاقة ارتباطية بين الالتزام الوظيفي والرضا الوظيفي عند أساتذة الجامعة الجزائرية، وقد تكونت عينة الدراسة من(139) أستاذ وأستاذة من جامعات الوسط الجزائري، تم اجرائها خلال الموسم الجامعي2018/2019 حيث أظهرت نتائج الدراسة انه، توجود علاقة ارتباطيه ايجابية بين درجة الرضا الوظيفي ومستوى الأداء الوظيفي ، وبينت أن هناك درجة متوسطة في الالتزام الوظيفي وفي مستوى الرضا الوظيفي عند أساتذة الجامعة. كما بينت الدراسة، وجود فروق ذات دلالة إحصائية في درجة الالتزام الوظيفي تعزى لمتغير الجنس ومتغير الخبرة المهنية، وقد أشارت الدراسة إل وجود فروق ذات دلالة إحصائية في مستوى الرضا الوظيفي تعزى لمتغير الجنس والخبرة، وعدم وجود فروق في متغير الدرجة العلمية.Abstract: The study aimed at identifying the existence of a correlation between job commitment and job satisfaction among the professors of the Algerian University.The sample of the study consisted of (139) professors and professors from the universities of the Algerian center during the academic year 2018/2019.The results of the study showed that there is a positive correlation between the degree of satisfaction Career and level of job performance, and showed that there is a moderate degree in the commitment to career and the level of job satisfaction among university professors. The study also showed that there are statistically significant differences in the degree of job commitment attributed to the gender variable and the variable of professional experience.The study indicated that there are statistically significant differences in the level of job satisfaction due to the variable of sex and experience, and the absence of differences in the degree of variable.
مقال
Keywords: الالتزام الوظيفي ، الرضا الوظيفي، الاستاذالجامعي; Job commitment, job satisfaction,University professor